Combined multiagent chemotherapy and radiotherapy is associated with prolonged overall survival in patients with non-operatively managed stage II-III pancreatic adenocarcinoma. Issue 4 (April 2022) - Sugumar, Kavin; Hue, Jonathan J.; Hardacre, Jeffrey M.; Ammori, John B.; Rothermel, Luke D.; Dorth, Jennifer; Saltzman, Joel; Mohamed, Amr; Selfridge, Jennifer E.; Bajor, David; Winter, Jordan M.; Ocuin, Lee M.
Abstract: Background: Most patients with pancreatic adenocarcinoma (PDAC) do not undergo surgical resection. The role of radiotherapy (RT) in non-operatively managed localized pancreatic adenocarcinoma is unclear. Methods: The National Cancer Database (2010–2016) was queried for patients with clinical stage II-III PDAC treated with multiagent systemic chemotherapy (CT) +/− RT but not surgery. Factors associated with the receipt of RT and overall survival were compared after adjusting for patient demographics and clinical characteristics. Results: A total of 14, 921 patients were included, of whom 9279 received CT and 5382 received CT + RT. Patients treated with CT + RT were more likely to be younger (65vs66yrs), treated at non-academic facilities (48.8%vs46.7%), have private insurance (40.3%vs36.5%), and have clinical T4 tumors (53.6%vs48.7%). Most patients who were treated with RT received external beam radiotherapy (89.3%), and the median dose was 5, 000 cGy. Median time to start of RT was 129 days. CT + RT was associated with longer overall survival (15.9vs11.8mos, p < 0.001), and remained associated with survival on multivariable analysis (HR 0.74, 95%CI 0.70–0.78). On a 4-month conditional survival analysis, combined CT + RT remained associated with improved survival compared to CT alone (16.0vs13.1mos, p < 0.001). Conclusions: In patients with non-operatively managed localized pancreatic adenocarcinoma, combined radiotherapy and multiagent systemic chemotherapy is associated with improved overall survival compared to chemotherapy alone.